P752 Oral once daily budesonide granules rapidly induce clinical remission in Lymphocytic Colitis: A double-blind, double-dummy, multi-centre, randomised trial. (16th January 2018) - Miehlke, S; Aust, D; Mihaly, E; Armerding, P; Böhm, G; Bonderup, O; Fernández-Bañares, F; Kupcinskas, J; Munck, L K; Rehbehn, K -U; Nacak, T; Greinwald, R; et al.
Abstract: Background: Lymphocytic colitis (LC) is a common cause of chronic, non-bloody diarrhoea. Budesonide appears to be effective based on small studies, but further randomised placebo-controlled trials were requested by recent Cochrane review. 1 Mesalazine has been proposed as a treatment option but no placebo-controlled trials have been reported. Thus, we performed a randomised, placebo-controlled, multicenter study to evaluate budesonide and mesalazine as induction therapy for lymphocytic colitis. Methods: Patients with active lymphocytic colitis were randomly assigned to either budesonide 9 mg once daily (Budenofalk® granules) or mesalazine 3 g once daily (Salofalk® granules), or placebo for 8 weeks in a double-blind, double-dummy design. The primary endpoint was clinical remission at week 8 defined by the Hjortswang-Criteria. 2 Secondary endpoints included median time to remission, histopathology and safety. Results: Final analysis included 57 patients (19 per group). Most patients were of female gender (72%) and mean age was 59 years. The proportion of patients in clinical remission at week 8 was significantly higher in the budesonide group than in the placebo group (intention-to-treat (ITT): 79% vs. 42%; p = 0.01). The difference in clinical remission at week 8 between mesalazine (63%) and placebo failed statistical significance ( p = 0.09). Median time to remission was significantly shorter in the budesonide group compared with placebo group (ITT: 3 days vs. 21 days, p = 0.04), whereas median time to remission in the mesalazine group was not significantly different compared with the placebo group (ITT: 12 days vs. 21 days, p = 0.21). The proportion of patients with histological remission at week 8 was higher with budesonide (68%) than with mesalazine (26%; p = 0.02) and placebo (21%; p = 0.008). The rate of adverse events did not differ among groups. Conclusions: Oral budesonide 9 mg once daily induces rapidly and highly effective clinical and histological remission in lymphocytic colitis in a safe manner, while oral mesalazine 3 g once daily was only numerically, but not statistically significant better than placebo. References: 1. Chande NAYN, Bhanji T, Nguyen TM, et al. Interventions for treating lymphocytic colitis (review) – cochrane analysis. Cochrane Database Syst Rev . 2017. 2. Hjortswang H, Tysk C, Bohr J, et al. Defining clinical criteria for clinical remission and disease activity in collagenous colitis. Inflamm Bowel Dis, 2009.